Development of sandwich panels combining fibre reinforced concrete layers and fibre reinforced polymer connectors: part II : evaluation of mechanical behaviour - Lameiras, Rodrigo Melo (2013)
In the first part of this paper the authors describe an innovative sandwich panel that comprises Glass Fibre Reinforced Polymer (GFRP) connectors and two thin layers of Steel Fibre Reinforced Self-Compacting Concrete (SFRSCC). This second part of the paper reports the investigation performed by the authors based on the numerical simulation of these sandwich panels. The simulations use the Finite Element Method (FEM) software implemented by the second author (FEMIX). Through linear static analyses and consideration of Ultimate Limit State loading scenarios, parametric studies were performed in order to optimise the arrangement of the GFRP connectors and the thickness of the SFRSCC layers. Moreover, models considering a specific nonlinear behaviour of SFRSCC were also constructed in order to simulate the progressive damage of the panel induced by cracking. In the scope of the nonlinear analyses, emphasis is given to parameter estimation of fracture modelling parameters for the fibre reinforced concrete based on both inverse analysis and the fib Model Code.